Compatibility of wild rootstocks in the production of cherry tomato seedlings - Guerra, Antônia Mirian Nogueira de Moura; Rodrigues, Ítalo José da Silva (Comunicata Scientiae, 2024)
Growing tomato crops is a highly significant activity in Brazil; however, several factors limit tomato productivity, mainly soil-borne diseases which, without proper control, can compromise the entire crop production. The proper use of grafting techniques emerges as an alternative to overcome barriers that limit tomato production in regions with unfavorable growth conditions. The use of rootstocks resistant to root diseases is seen as a viable option for tomato production. In this context, the objective of this work was to evaluate the compatibility and efficiency of rootstocks for cherry tomatoes. A randomized block design was used, with five treatments and four replications; each plot consisted of 36 grafted seedlings. The treatments consisted of rootstocks of Eggplant, Jurubeba, Jilo, and Tomato (Intacto; Feltrin Sementes®), and a Control (cherry tomato without grafting). All rootstocks were compatible with cherry tomatoes. Moreover, seedlings grafted onto Jurubeba rootstocks presented results closest to the Control (cherry tomatoes). Seedlings grafted onto Jurubeba and Eggplant rootstocks presented the best results regarding vegetative development and total dry matter accumulation. Jurubeba and Eggplant rootstocks are viable alternatives for grafting cherry tomato seedlings. All utilized rootstocks can be further investigated for their resistance to root diseases affecting tomato crops.